The quiet American [videorecording (DVD)] - Noyce, Phillip; Caine, Michael; Fraser, Brendan, 1968-; Đỗ, Thị Hải Yến. 1982-; Greene, Graham, 1904-1991 (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2003)
A story that led to the events of the United States military involvement in Vietnam. Here, a love triangle between a British journalist, his mistress, and a mysterious CIA operative evolves into a much greater mystery that eventually leads to murder and deception.